Poczucie prawnego bezpieczeństwa w warunkach transformacji systemowej - Pawłowska, Barbara; Drozdowski, Rafał (Wydział Prawa i Administracji UAM, 1995)
The first part of the paper focuses on the discussion of a number of the most typical features observed in the transition period which in the opinion of many Poles, were the most influential factors generating the feeling of low level of legal security experienced by many in the years 1992 -1993. On this background, several instruments which may reduce the feeling of a lack of'institutionalised security' are presented. Those solutions have emerged in conditions when a new political, economic and social order is created and they include such instruments as eg. handing over to the mass media a function of an effective temporary citizens intervention institution, expecting that the media and business sphere would assume a role of a substitute of the official social care and welfare system, or the treating of the institution of the ombudsman as a place where every social claim and demand can be addressed. All such functions have been previously assumed by the state or rather its party structures. In the author's opinion the reality today is that they are presently merely prostheses acting in place of the real state, being its temporary and inadequate substitute. What is more, they unintentionally petrify the system in which the dominance of nonstandardised and non-formal procedures is still well maintained.
The feeling of legal security in the conditions of system transformations